Peer effects in parental leave: Evidence from Italy - Dottori, Davide; Modena, Francesca; Tanzi, Giulia Martina (Labour economics, 2024)
In this paper we estimate peer effects in parental leave (PL), analyzing whether mothers’ choices may be influenced by prior decisions made by their female colleagues. We identify peer effects through an exogenous variation in the probability that peers take a PL driven by a reform implemented in Italy in 2015 which extended the time period over which parents can receive a paid PL, providing greater flexibility in its use. We focus on post-reform mothers and exploit the heterogeneity in the share of their peers who, due to their children’s age, have been affected by the reform. Our findings show the existence of important peer effects: a 10 percentage point increase in the share of peers that took a PL in response to the reform results in mothers being 2.4 percentage points more likely to take a PL. We also find a positive effect on the amount of PL taken and a negative effect on the probability of working part-time. As suggested by the heterogeneity analysis, the peer effects seem to be particularly evident for mothers with a low tenure in the firm and in workplaces characterized by strong interactions among the colleagues. •We estimate peer effects in parental leaves’ decisions (PL) of mothers.•We exploit a variation in the cost of PL, due to a reform implemented in Italy.•Higher shares of peers that took a PL result in mothers being more likely to take it.•The effect is higher for mothers with a low experience in the firm.•The effect increases in contexts with stronger interactions among colleagues.